The Arquivo da Comarca Judicial de Benguela: Problems and Potentialities - Catarina Madeira-Santos, José C. Curto, Frank J. Luce (Africana Studia, 2020)
Social scientists have, for some time now, suspected that the Arquivo Histórico of the Comarca Judicial de Benguela houses documentation that can significantly expand our understanding of the nineteenth century in this central Angolan port town, a period characterized, amongst other processes, by the transition from the late trans-Atlantic slave trade to the so-called era of legitimate commerce. Our contribution details the tribulations that one team of international researchers experienced in attempting to access the historical documentary holdings of this small, dormant, and endangered archive in Benguela. It includes an inventory of nearly 150 court files relating to the second half of the nineteenth century, including the names of the litigants and the subject matter of the litigation. The inventory suggests that the files contain documents of significant value for the reconstruction of this period in Benguela’s past through reference to the town’s trading and propertied families, their extended family relations, their landholdings, and their commercial property. We speculate that the judicial authorities may yet be unwilling to have this information come to light. Keywords: Benguela, archive,judiciary, history, estate inventories, property, wealth, gender.